Investigating the relationship between foreign language anxiety in the four skills and year of study among Yemeni University EFL learners - Yassin, Amr Abdullatif; Norizan Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aimed to investigate the relationship between foreign language anxiety and the year of study among Yemeni university EFL learners. The data were collected from the English language students from years 1 to 4 of the Faculty of Arts, Ibb University, Yemen. The data were collected using Foreign Language Anxiety Scale (FLAS) which measures the level of anxiety in the four skills of listening, speaking, reading and writing. The data were analysed using SPSS version 22 and one-way Anova is used to determine if there is a significant difference in the level of anxiety between the students in the four years. The results revealed that second year students experienced the highest level of anxiety followed by third year, fourth year and the first year students experienced the least level of anxiety. However, no significance difference was found between the level of foreign language anxiety and the year of study. The study concluded that two other factors, the interference of the mother tongue and novelty effect, might have affected the relationship between language anxiety and year of study. Implications of the study are also discussed.